A NAV a Day Keeps the Inefficiency Away? Fund Trading Strategies using Daily Values - Hughen,J. C.; Mathew,Prem; Ragan,K. (Financial Services Review, 2005)
Previous research documents the value of closed-end fund trading rules based on the size of theweekly discount. The growing number of closed-end funds that provide daily net asset value data provides an opportunity to test the profitability of short-term fund trading strategies. We find that short-term trading strategies that purchase fund shares after large negative discount changes are profitable, on average, even when transaction costs are incorporated. However, strategies that short sell fund shares after large positive discount changes do not produce an average profit. The limited amount of trading in closed-end funds may make it difficult to achieve short-term profits from discount fluctuations. © 2005 Academy of Financial Services. All rights reserved.
Keywords: Finance